Smart Cities Mission in India: some definitions and considerations. Issue 4 (2nd September 2019) - Prakash, Anand
Abstract : Purpose: The purpose of this paper is to outline the generic concepts and learning about smart cities and capture the varied perspectives of winning case examples in India. An attempt is made in the paper to study the available literature about smart cities and structure them into a synoptic framework of planning, design and implementation. Design/methodology/approach: This paper has followed a case study approach and complied multi-facet 18 features of 99 winners of "100 Smart Cities Mission" in India to showcase trends and developments of tomorrow. These multi-facet features collectively provide a heterogeneous view of the future potentials of smart cities in India. Findings: Findings of this research can contribute to shaping a number significant learning of different aspects of policy formation in India with respect to smart cities in view of the sensitivity of citizen participation in the individualized society of information age. Research limitations/implications: The results and learning of this study have not been verified empirically through a survey and they are based on qualitative incidences in the submitted proposal. Further, the state of this paper is generic and there is a lack of city-specific context specification except for some illustrations of success stories and upcoming innovative projects. Practical implications: This paper provides a better understanding of current practices fulfilling featured requirements of smart cities to identify opportunities for improvement based on the current state of the debate. Social implications: The development of smart cities in India is expected to play an outstanding role in shaping the world of tomorrow. Although the focus of this development is on the actual needs and requirements of today; however, some trends and predictions of the future society can also be identified. Originality/value: This paper is the original attempt to set the definition of developing and replicating smart cities in India based on decisive parameters and it contributes to meet challenges of urban planning.